THE CITY CENTER IN THE STRUCTURE(ING) URBAN CONTEXT: CONSIDERATIONS ABOUT CONVENTIONAL URBAN THEORY AND CRITICAL URBAN THEORY - Soares Pereira, Claudio Smalley [UNESP] (Univ Estado Rio Janeiro, 2017)
This paper discusses city center notions and also the centrality process in the structure(ing) study context. Considers such notions in the conventional urban theory science perspective along with his contributions to the city and the urban space study, and about the critical urban theory/science contribution, focusing in more detail the Henri Lefebvre and Manuel Castells contributions on the subject on screen. Finally, closes with some thoughts about the role of urban critical theory today.
Keywords: city center; centrality; structure; strucruraction; urban theory